Management of Project Child Indonesia Organizations During The Covid-19 Pandemic: Manajemen Organisasi Project Child Indonesia Selama Pandemi Covid-19 - Yusuf, Mirna (Progress In Social Development, 2021)
ABSTRACT:So far, the literature that looks at the relationship between community organizations and the Covid-19 pandemic tends to see community organizations only as subjects that have a big influence and role in helping the community to deal with Covid-19. However, no one has seen the relationship between community organizations and the Covid-19 pandemic by seeing community organizations as objects of the presence of the pandemic. So that researchers want to see further how community organizations deal with the Covid-19 pandemic as a disaster. More specifically, researchers want to analyze the adaptation of community organizations to the presence of Covid-19 as part of organizational disaster management. This will then be seen in more detail by taking one of the cases in a community organization based on empowerment in the fields of education and poverty alleviation, namely Project Child Indonesia. The topic of organizational adaptation will be the main topic of this paper. ABSTRAK:Selama ini literatur yang melihat hubungan organisasi masyarakat dengan pandemi Covid-19 cendrung melihat organisasi masyarakat hanya sebagai subjek yang memiliki pengaruh dan peran besar dalam membantu masyarakat untuk menangani Covid-19. Akan tetapi belum ada yang melihat hubungan organisasi masyarakat dan pandemi Covid-19 dengan melihat organisasi masyarakat sebagai objek dari hadirnya pandemi tersebut. Sehingga peneliti ingin melihat lebih lanjut bagaimana organisasi masyarakat dalam menghadapi pandemi Covid-19 sebagai sebuah bencana. Lebih khusus peneliti ingin menganalisis adaptasi organisasi masyarakat terhdap hadirnya Covid-19 sebagai bagian dari manajemen bencana organisasi. Hal ini kemudian akan dilihat lebih rinci dengan mengambil salah satu kasus pada organsasi masyarakat yang berbasis pada pemberdayaan di bidang pendidikan dan pengentasan kemiskinan yaitu Project Child Indonesia. Topik mengenai adaptasi organisasi akan menjadi topik bahasan utama tulisan ini.